Shared Delusional Parasitosis in Two Families: Clinical Insights Into Folie à Deux and Folie à Trois - Gökçe Işıl Kurmuş; Hanife Karataş; Elif Erdem; Süheyla Doğan Bulut; Müzeyyen Gönül; Selda Pelin Kartal (JMIR Dermatology)
AbstractDelusional parasitosis is a rare psychotic disorder characterized by individuals firmly believing that they are infested with parasites despite no medical evidence. It may be shared among close contacts—termed folie à deuxfolie à trois